Unplanned Postoperative Reintubation in Children with Bronchial Asthma - Winch, Peter D.; Mpody, Christian; Murray-Torres, Teresa M.; Rudolph, Shannon; Tobias, Joseph D.; Nafiu, Olubukola O. (Journal of Pediatric Intensive Care, 2021)
Unplanned postoperative reintubation is a serious complication that may increase postsurgical hospital length of stay and mortality. Although asthma is a risk factor for perioperative adverse respiratory events, its association with unplanned postoperative reintubation in children has not been comprehensively examined. Our aim was to determine the association between a preoperative comorbid asthma diagnosis and the incidence of unplanned postoperative reintubation in children. This was a retrospective cohort study comprising of 194,470 children who underwent inpatient surgery at institutions participating in the National Surgical Quality Improvement Program–Pediatric. The primary outcome was the association of preoperative asthma diagnosis with early, unplanned postoperative reintubation (within the first 72 hours following surgery). We also evaluated the association between bronchial asthma and prolonged hospital length of stay (longer than the 75th percentile for the cohort). The incidence of unplanned postoperative reintubation in the study cohort was 0.5% in patients with a history of asthma compared with 0.2% in patients without the diagnosis (odds ratio [OR]: 2.23, 95% confidence interval [CI]: 1.71–2.89). This association remained significant after controlling for several clinical characteristics (OR: 1.54, 95% CI: 1.17–2.20). Additionally, asthmatic children were more likely to require a hospital length of stay longer than the 75th percentile for the study cohort (adjusted OR: 1.05, 95% CI: 1.01–1.10). Children with preoperative comorbid asthma diagnosis have an increased incidence of early, unplanned postoperative reintubation and prolonged postoperative hospitalization following inpatient surgery. By identifying these patients as having higher perioperative risks, it may be possible to institute strategies to improve their outcomes.
Keywords: asthma; early unplanned reintubation; pediatric